ANDROID-BASED MAID RECOMMENDATION - Muhammad Ihsan; Rila Mandala (President University, 2021)
Maidsareanimportantpartofthehousehold, in this case problems arise related to peoplewhohavehighactivitiessuchascareerwomen,including housewives, or other families. The dailyroutine which is quite dense makes them unable to doall household chores by themselves. Due to his busy lifein order to complete household chores, a householdassistant is needed. One solution to the above problemsis the availability of an Android-based application formaid recommendations. This application was createdto make it easy for consumers to find a maid quicklyand easily. This application can display various serviceproviders with complete and detailed information tomake it easier for consumers to choose the servicesneeded.